Method for manufacturing positive electrode and positive electrode
The described manufacturing method for positive electrodes in lithium ion secondary batteries, utilizing specific carbon nanotubes and slurry viscosity, addresses the output limitations of conventional electrodes by creating optimal conductive and ion flow paths, enhancing battery performance.
Patent Information
- Application Number
- JP2023092047
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-05
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2043-06-05
AI Technical Summary
Conventional positive electrodes in lithium ion secondary batteries do not adequately enhance output characteristics, necessitating improvements for higher performance in vehicle drive power sources.
A manufacturing method involving coating a positive electrode current collector with a slurry containing a positive electrode active material, carbon nanotubes, and a dispersion medium, followed by drying and pressing to achieve a porosity of 42.5% to 54.5% and using carbon nanotubes with an average length of 0.3 μm to 0.7 μm and a slurry viscosity of 2.1 Pa·s to 4.2 Pa·s.
This method results in a positive electrode that enhances the output characteristics of lithium ion secondary batteries by forming a suitable conductive path and ion flow path, thereby improving battery performance.
Smart Images

Figure 2024174297000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing a positive electrode.The present invention also relates to a positive electrode. [Background technology]
[0002] 2. Description of the Related Art In recent years, lithium ion secondary batteries have been suitably used as portable power sources for personal computers, mobile terminals, and the like, and as power sources for driving vehicles such as electric vehicles (BEVs), hybrid electric vehicles (HEVs), and plug-in hybrid electric vehicles (PHEVs), among others.
[0003] As lithium-ion secondary batteries become more widespread, there is a demand for higher output, particularly in applications as vehicle drive power sources. One method for increasing the output of lithium-ion secondary batteries is known to be the use of carbon nanotubes as a conductive material in the positive electrode (see, for example, Patent Documents 1 to 4). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2022-37549 A [Patent Document 2] Patent Publication No. 2022-55889 [Patent Document 3] JP 2015-185229 A [Patent Document 4] JP 2015-195143 A Summary of the Invention [Problem to be solved by the invention]
[0005] As a result of intensive research, the present inventors have found that there is still room for improvement in the positive electrodes of the conventional technology in terms of increasing the output of lithium ion secondary batteries.
[0006] Therefore, an object of the present invention is to provide a positive electrode capable of imparting excellent output characteristics to a lithium ion secondary battery. [Means for solving the problem]
[0007] The method for producing a positive electrode disclosed herein includes the steps of: applying a positive electrode slurry containing a positive electrode active material, carbon nanotubes, and a dispersion medium to a positive electrode current collector; drying the applied positive electrode slurry to form a positive electrode active material layer; and pressing the positive electrode active material layer so that the positive electrode active material layer has a porosity of 42.5% to 54.5%. The carbon nanotubes have an average length of 0.3 μm to 0.7 μm. The positive electrode slurry has a viscosity of 2.1 Pa·s to 4.2 Pa·s at 25° C.
[0008] According to this configuration, it is possible to provide a positive electrode that can impart excellent output characteristics to a lithium ion secondary battery.
[0009] From another aspect, the positive electrode disclosed herein includes a positive electrode current collector and a positive electrode active material layer supported by the positive electrode current collector. The positive electrode active material layer contains a positive electrode active material and carbon nanotubes. The positive electrode active material layer has a porosity of 42.5% to 54.5%. The carbon nanotubes have an average length of 0.3 μm to 0.7 μm. The positive electrode is formed using a positive electrode slurry having a viscosity at 25° C. of 2.1 Pa·s to 4.2 Pa·s.
[0010] According to this configuration, it is possible to provide a positive electrode that can impart excellent output characteristics to a lithium ion secondary battery. [Brief description of the drawings]
[0011] [Figure 1] 2 is a flowchart showing each step of a method for producing a positive electrode according to one embodiment of the present invention. [Diagram 2] FIG. 2 is a schematic cross-sectional view of an example of a positive electrode obtained by a production method according to one embodiment of the present invention. [Diagram 3] FIG. 3 is a cross-sectional view that illustrates a schematic configuration of a lithium-ion secondary battery constructed using the positive electrode of FIG. 2. [Figure 4] 4 is a schematic exploded view showing the configuration of a wound electrode body of the lithium ion secondary battery of FIG. 3. [Diagram 5] 1 is a graph plotting the value of initial output resistance for various slurry viscosities versus the porosity of the positive electrode active material layer when carbon nanotubes with an average length of 0.1 μm are used. [Figure 6] 1 is a graph plotting values of initial output resistance for various slurry viscosities versus the porosity of a positive electrode active material layer when carbon nanotubes with an average length of 0.3 μm are used. [Figure 7] 1 is a graph plotting values of initial output resistance for various slurry viscosities versus the porosity of a positive electrode active material layer when carbon nanotubes with an average length of 0.5 μm are used. [Figure 8] 1 is a graph plotting values of initial output resistance for various slurry viscosities versus the porosity of a positive electrode active material layer when carbon nanotubes with an average length of 0.7 μm are used. [Figure 9] 1 is a graph plotting values of initial output resistance for various slurry viscosities versus the porosity of a positive electrode active material layer when carbon nanotubes with an average length of 1.0 μm are used. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] Hereinafter, an embodiment of the present invention will be described with reference to the drawings. Matters not mentioned in this specification but necessary for carrying out the present invention can be understood as design matters for a person skilled in the art based on the prior art in the relevant field. The present invention can be carried out based on the contents disclosed in this specification and the technical common sense in the relevant field. In addition, in the following drawings, members and parts having the same function are described with the same reference numerals. Furthermore, the dimensional relationships (length, width, thickness, etc.) in each drawing do not reflect the actual dimensional relationships. In addition, the numerical range expressed as "A to B" in this specification includes A and B.
[0013] In this specification, the term "secondary battery" refers to an electricity storage device that can be repeatedly charged and discharged. In addition, in this specification, the term "lithium ion secondary battery" refers to a secondary battery that uses lithium ions as a charge carrier and realizes charging and discharging by the transfer of charge associated with the lithium ions between the positive and negative electrodes.
[0014] In this specification, the term "slurry" refers to a mixture in which a part or all of the solid content is dispersed in a dispersion medium, and includes so-called "paste", "ink", and the like.
[0015] Hereinafter, as an example, an embodiment in which the positive electrode obtained by the production method disclosed herein is a positive electrode for a lithium ion secondary battery will be specifically described with reference to the drawings.
[0016] As shown in Fig. 1, the method for producing a positive electrode according to this embodiment includes a step (hereinafter also referred to as a "coating step") S101 of coating a positive electrode current collector with a positive electrode slurry containing a positive electrode active material, carbon nanotubes (CNTs), and a dispersion medium, a step (hereinafter also referred to as a "drying step") S102 of drying the coated positive electrode slurry to form a positive electrode active material layer, and a step (hereinafter also referred to as a "pressing step") S103 of pressing the positive electrode active material layer so that the porosity of the positive electrode active material layer is 42.5% to 54.5%. The average length of the carbon nanotubes is 0.3 µm to 0.7 µm. The viscosity of the positive electrode slurry at 25°C is 2.1 Pa·s to 4.2 Pa·s.
[0017] Each step will be described below by taking as an example the case of producing a positive electrode shown in Fig. 2. Fig. 2 is a cross-sectional view taken along the width and thickness directions of the positive electrode.
[0018] 2 includes a positive electrode current collector 52 and a positive electrode active material layer 54 supported on the positive electrode current collector 52. In the illustrated example, the positive electrode active material layer 54 is provided on both sides of the positive electrode current collector 52, but may be provided on one side. The positive electrode active material layer 54 is preferably provided on both sides of the positive electrode current collector 52.
[0019] As shown in the illustrated example, the positive electrode 50 may have a positive electrode active material layer-free portion 52a at least at one end where the positive electrode active material layer 54 is not formed and the positive electrode current collector 52 is exposed. The positive electrode active material layer-free portion 52a functions as a current collector. However, the form of the current collector in the positive electrode 50 is not limited thereto.
[0020] First, the coating step S101 will be described. In this step S101, a positive electrode slurry containing a positive electrode active material, carbon nanotubes (CNTs), and a dispersion medium is coated onto a positive electrode current collector. The average length of the carbon nanotubes is 0.3 μm to 0.7 μm. The viscosity of the positive electrode slurry at 25° C. is 2.1 Pa·s to 4.2 Pa·s.
[0021] The positive electrode current collector 52 used in the coating step S101 may be a sheet or foil made of a metal such as aluminum, nickel, titanium, or stainless steel, and aluminum foil is preferred. When aluminum foil is used as the positive electrode current collector 52, its thickness is not particularly limited, but is, for example, 5 μm or more and 35 μm or less, and preferably 7 μm or more and 20 μm or less.
[0022] The positive electrode active material contained in the positive electrode slurry may be a known positive electrode active material used in lithium ion secondary batteries.Specifically, for example, the positive electrode active material may be a lithium composite oxide, a lithium transition metal phosphate compound, or the like.The crystal structure of the positive electrode active material is not particularly limited, and may be a layered structure, a spinel structure, an olivine structure, or the like.
[0023] The lithium composite oxide is preferably a lithium transition metal composite oxide containing at least one of Ni, Co, and Mn as a transition metal element, and specific examples thereof include lithium nickel composite oxide, lithium cobalt composite oxide, lithium manganese composite oxide, lithium nickel manganese composite oxide, lithium nickel cobalt manganese composite oxide, lithium nickel cobalt aluminum composite oxide, and lithium iron nickel manganese composite oxide. These positive electrode active materials may be used alone or in combination of two or more. The positive electrode active material is preferably a lithium nickel cobalt manganese composite oxide.
[0024] In this specification, the term "lithium nickel cobalt manganese composite oxide" includes oxides containing Li, Ni, Co, Mn, and O as constituent elements, as well as oxides containing one or more additional elements other than those. Examples of such additional elements include transition metal elements and typical metal elements such as Mg, Ca, Al, Ti, V, Cr, Y, Zr, Nb, Mo, Hf, Ta, W, Na, Fe, Zn, and Sn. The additional element may be a semimetal element such as B, C, Si, or P, or a nonmetal element such as S, F, Cl, Br, or I. This also applies to the above-mentioned lithium nickel composite oxide, lithium cobalt composite oxide, lithium manganese composite oxide, lithium nickel manganese composite oxide, lithium nickel cobalt aluminum composite oxide, and lithium iron nickel manganese composite oxide.
[0025] Examples of the lithium transition metal phosphate compound include lithium iron phosphate (LiFePO4), lithium manganese phosphate (LiMnPO4), and lithium manganese iron phosphate.
[0026] The above positive electrode active materials can be used alone or in combination of two or more.
[0027] The average particle diameter of the positive electrode active material is not particularly limited, but is, for example, 0.5 μm to 30 μm, preferably 1 μm to 20 μm, more preferably 1.5 μm to 10 μm, and even more preferably 2 μm to 5 μm. In this specification, the term "average particle diameter" refers to the median diameter (D50), and therefore means the particle diameter corresponding to a cumulative frequency of 50 volume % from the fine particle side with a small particle diameter in the volume-based particle size distribution based on the laser diffraction / scattering method. Therefore, the average particle diameter (D50) can be determined using a known laser diffraction / scattering type particle size distribution measuring device or the like.
[0028] The amount of the positive electrode active material used is not particularly limited, but is preferably 87 mass % or more, more preferably 90 mass % or more, and even more preferably 96 mass % or more, of the total solid content of the positive electrode slurry (i.e., relative to the total mass of the solid content of the positive electrode slurry).
[0029] The type of CNT contained in the positive electrode slurry is not particularly limited, and for example, single-walled carbon nanotubes (SWCNT), double-walled carbon nanotubes (DWCNT), multi-walled carbon nanotubes (MWCNT), etc. can be used. These can be used alone or in combination of two or more. As the CNT, MWCNT is preferable. The CNT may be manufactured by an arc discharge method, a laser ablation method, a chemical vapor deposition method, etc.
[0030] The average length of the CNTs is 0.3 μm to 0.7 μm. When the average length of the CNTs is within this range, a good conductive path can be formed between the positive electrode active materials, which contributes to high output of the lithium ion secondary battery. From the viewpoint of imparting a higher output to the lithium ion secondary battery, the average length of the CNTs is preferably 0.5 μm to 0.7 μm.
[0031] The average length of the CNTs can be determined as the average value of the equivalent spherical diameter (ESD) using a flow imaging microscope (eg, "FlowCam nano" manufactured by Yokogawa Electric Corporation).
[0032] The average diameter of the CNTs is not particularly limited and is, for example, 0.1 nm to 50 nm, preferably 1 nm to 40 nm, and more preferably 2 nm to 30 nm.
[0033] The average diameter of CNTs can be obtained by taking an electron microscope photograph of CNTs and averaging the diameters of 100 or more CNTs. Specifically, for example, a CNT dispersion is diluted and then dried to prepare a measurement sample. This sample is observed with a scanning electron microscope to obtain the diameters of 100 or more CNTs and calculate the average value. At this time, if the CNTs are re-aggregated, the diameter is obtained for the bundle of aggregated CNTs.
[0034] The amount of CNT used is not particularly limited. If the amount of CNT used is too small, the effect as a conductive material may be reduced. On the other hand, if the amount of CNT used is too large, the positive electrode slurry may be thickened. Therefore, the amount of CNT used is preferably 0.1 mass% or more and 3.0 mass% or less, more preferably 0.3 mass% or more and 2.5 mass% or less, and even more preferably 0.5 mass% or more and 2.0 mass% or less, based on the total solid content of the positive electrode slurry (i.e., the total mass of the solid content of the positive electrode slurry).
[0035] The dispersion medium contained in the positive electrode slurry is also called "solvent" in the technical field. As the dispersion medium, a dispersion medium (particularly an organic solvent) used in a known positive electrode slurry for a lithium ion secondary battery can be used. A suitable example of the dispersion medium is N-methyl-2-pyrrolidone (NMP).
[0036] The amount of the dispersion medium used is not particularly limited as long as it can disperse the positive electrode active material and CNTs. The viscosity of the positive electrode slurry can be easily controlled by adjusting the amount of the dispersion medium used. Therefore, the dispersion medium is preferably used in an amount such that the viscosity of the positive electrode slurry at 25°C is 2.1 Pa·s to 4.2 Pa·s.
[0037] The positive electrode slurry may contain components (optional components) other than the positive electrode active material, CNT, and dispersion medium. Examples of the optional components include a CNT dispersion medium and a binder.
[0038] A CNT dispersant is an additive that stably disperses or solubilizes CNTs in a dispersion medium, and is also called a solubilizer. Examples of CNT dispersants that can be used include surfactant-type dispersants (also called low-molecular-weight dispersants), polymer-type dispersants, and inorganic-type dispersants. The CNT dispersant may be anionic, cationic, amphoteric, or nonionic. Thus, the CNT dispersant may have at least one functional group selected from the group consisting of anionic groups, cationic groups, and nonionic groups in its molecular structure. The surfactant refers to an amphiphilic substance that has a chemical structure in which a hydrophilic portion and a lipophilic portion are bonded together by a covalent bond in its molecular structure.
[0039] Specific examples of CNT dispersants include polycondensation aromatic surfactants such as sodium salt of naphthalenesulfonic acid formalin condensate, ammonium salt of naphthalenesulfonic acid formalin condensate, and sodium salt of methylnaphthalenesulfonic acid formalin condensate; polycarboxylic acids and their salts, such as polyacrylic acid and its salts, polymethacrylic acid and its salts; triazine derivative dispersants (preferably containing a carbazolyl group or a benzimidazolyl group); polyvinylpyrrolidone (PVP); polymers having polynuclear aromatics such as pyrene and anthracene in the side chain; polynuclear aromatic ammonium derivatives such as pyrene ammonium derivatives (e.g., compounds in which an ammonium bromide group is introduced into pyrene) and anthracene ammonium derivatives; and the like. These CNT dispersants can be used alone or in combination of two or more. As the CNT dispersant, those containing polynuclear aromatics are preferable. Specifically, as the CNT dispersant, polymers having polynuclear aromatics in the side chain and polynuclear aromatic ammonium derivatives are preferable.
[0040] The ratio of the CNT dispersant to the CNT may be appropriately determined depending on the type of CNT and CNT dispersant. Here, if the ratio of the CNT dispersant is too small, the dispersibility may be insufficient. On the other hand, if the ratio of the CNT dispersant is too large, the CNT dispersant may adhere excessively to the CNT surface, which may cause an increase in resistance. When the CNT is SWCNT, the amount of the CNT dispersant used is, for example, 1 part by mass to 400 parts by mass, and preferably 20 parts by mass to 200 parts by mass, relative to 100 parts by mass of CNT. When the CNT is MWNT, the amount of the CNT dispersant used is, for example, 1 part by mass to 100 parts by mass, and preferably 4 parts by mass to 40 parts by mass, relative to 100 parts by mass of CNT.
[0041] As the binder, for example, polyvinylidene fluoride (PVdF) or the like can be used. The molecular weight of the binder may be the same as that of a known binder used in the positive electrode of a secondary battery. PVdF is typically a homopolymer, but may be copolymerized with other monomer units other than vinylidene fluoride within a range that does not impair the effects of the present invention (for example, 10 mol% or less of all monomer units).
[0042] The amount of the binder used is not particularly limited, but is, for example, 0.1 mass % to 10 mass %, preferably 0.2 mass % to 5 mass %, and more preferably 0.3 mass % to 2 mass %, of the total solid content of the positive electrode slurry (i.e., relative to the total mass of the solid content of the positive electrode slurry).
[0043] The positive electrode slurry can be prepared by mixing the positive electrode active material, CNTs, a dispersion medium, and optional components according to a known method.
[0044] Here, the viscosity of the positive electrode slurry used in the coating step S101 at 25° C. is 2.1 Pa·s to 4.2 Pa·s. When the viscosity of the positive electrode slurry is within this range, the CNTs can be uniformly dispersed in the positive electrode active material layer 54, and a good conductive path can be formed throughout the positive electrode active material layer 54. This also contributes to increasing the output of the lithium-ion secondary battery.
[0045] The viscosity of the positive electrode slurry can be controlled by adjusting the content of each component. In particular, it is easy to control the viscosity by adjusting the content of the dispersion medium in the positive electrode slurry. Alternatively, it can be adjusted by changing the molecular weight of the binder, the average length of the CNTs, the content of the CNTs, etc.
[0046] The viscosity of the positive electrode slurry was measured using an E-type viscometer at 25°C and a shear rate of 10 sec. -1 It can be determined by measuring under the following conditions.
[0047] The order of mixing the components of the positive electrode slurry is not particularly limited. Since CNTs have low dispersibility, it is preferable to first disperse the CNTs in a dispersion medium from the viewpoint of preparing the positive electrode slurry in a short time. When dispersing, it is advantageous to perform ultrasonic irradiation or the like in order to disperse the CNTs in a short time. Then, the positive electrode active material and optional components (e.g., binder, etc.) are added and mixed using a known stirring device (e.g., planetary mixer, etc.), so that a slurry in which each component is uniformly dispersed can be easily prepared.
[0048] The positive electrode slurry can be applied according to a known method. For example, the positive electrode slurry can be applied onto the positive electrode current collector using a coating device such as a slit coater, a die coater, a comma coater, a gravure coater, or a dip coater. The amount of the positive electrode slurry to be applied may be appropriately determined in consideration of the thickness, basis weight, etc. of the positive electrode active material layer 54.
[0049] When the positive electrode 50 shown in FIG. 2 is produced, the positive electrode slurry is applied to both sides of the positive electrode collector 52. However, when the positive electrode active material layer 54 is formed only on one side of the positive electrode collector 52 in the positive electrode 50, the positive electrode slurry is applied to one side of the positive electrode collector. Moreover, by applying the positive electrode slurry along one end in the width direction of the positive electrode collector 52 while preventing the positive electrode slurry from being applied to the other end, a positive electrode active material layer non-formed portion 52a can be provided. The coating step S101 can be performed in the above manner.
[0050] Next, the drying step S102 will be described. In the drying step S102, the applied positive electrode slurry is dried to form a positive electrode active material layer. The drying step S102 can be performed according to a known method.
[0051] Specifically, for example, the dispersion medium can be removed from the positive electrode slurry applied to the positive electrode current collector using a drying device such as a drying oven. The drying temperature and drying time can be appropriately determined according to the type and amount of the dispersion medium contained in the positive electrode slurry, and are not particularly limited. The drying temperature is, for example, 70°C to 200°C (particularly, 110°C to 180°C). The drying time is, for example, 20 seconds to 120 minutes.
[0052] Next, the pressing step S103 will be described. In the pressing step S103, the positive electrode active material layer 54 is pressed so that the positive electrode active material layer 54 has a porosity of 42.5% to 54.5%. This pressing can be performed according to a known method (for example, roll pressing).
[0053] Here, by adjusting the pressing conditions, the porosity of the positive electrode active material layer 54 can be controlled to 42.5% to 54.5%. For example, when the pressing process is performed by roll pressing, the porosity of the positive electrode active material layer 54 can be controlled by changing the linear pressure or the gap between the rolls.
[0054] In general, from the viewpoint of high energy density of the positive electrode, it is preferable that the porosity of the positive electrode active material layer 54 is low (for example, in a positive electrode with high energy density, the porosity is usually set to 25% or less). However, in this embodiment, the porosity of the positive electrode active material layer 54 is intentionally set to be high. Therefore, the non-aqueous electrolyte is easily impregnated into the positive electrode active material layer 54, and a flow path for Li ions can be suitably formed in the positive electrode active material during discharge of the lithium ion secondary battery. This also contributes to high output. From the viewpoint of a higher output improvement effect, the porosity of the positive electrode active material layer 54 is preferably 45% to 54%, and more preferably 46% to 53%. The porosity of the positive electrode active material layer 54 can be determined by measurement by mercury intrusion porosimeter. The measurement can be performed according to a known method using a commercially available mercury intrusion porosimeter.
[0055] In this way, by using CNTs with an average length of 0.3 μm to 0.7 μm, using a positive electrode slurry with a viscosity of 2.1 Pa·s to 4.2 Pa·s at 25° C., and setting the porosity of the positive electrode active material layer to 42.5% to 54.5% by pressing, it is possible to form a good conductive path throughout positive electrode active material layer 54 while also forming a flow path for Li ions. As a result, it is possible to increase the output of a lithium ion secondary battery using positive electrode 50.
[0056] In the obtained positive electrode 50, the thickness of the positive electrode active material layer 54 per side is not particularly limited, but is, for example, from 10 μm to 300 μm, and preferably from 20 μm to 200 μm.
[0057] A protective layer may be further provided on the positive electrode active material layer non-forming portion 52a adjacent to the positive electrode active material layer 54. The protective layer is, for example, an insulating layer containing ceramic particles or the like. The protective layer can be formed according to a known method.
[0058] In addition, a step of cutting the positive electrode active material layer-free portion 52a into a predetermined shape by a laser or the like may be further performed. By processing the positive electrode active material layer-free portion 52a into a predetermined shape, a current collecting tab or the like can be formed.
[0059] The positive electrode 50 obtained by the manufacturing method disclosed herein can be used as a positive electrode for a secondary battery (particularly a lithium ion secondary battery) according to known methods.
[0060] From another perspective, a positive electrode 50 disclosed herein includes a positive electrode current collector 52 and a positive electrode active material layer 54 supported by the positive electrode current collector 52. The positive electrode active material layer 54 contains a positive electrode active material and carbon nanotubes. The positive electrode active material layer 54 has a porosity of 42.5% to 54.5%. The carbon nanotubes have an average length of 0.3 μm to 0.7 μm. The positive electrode 50 is formed using a positive electrode slurry having a viscosity of 2.1 Pa s to 4.2 Pa s at 25° C.
[0061] As an example of a secondary battery using the positive electrode 50, a configuration example of a lithium ion secondary battery using the positive electrode 50 will be described below with reference to the drawings.
[0062] The lithium ion secondary battery 100 shown in FIG. 3 is a sealed battery constructed by housing a flat wound electrode body 20 and a nonaqueous electrolyte 80 in a flat rectangular battery case (i.e., an outer container) 30. The battery case 30 is provided with a positive electrode terminal 42 and a negative electrode terminal 44 for external connection, and a thin-walled safety valve 36 that is set to release the internal pressure when the internal pressure of the battery case 30 rises to a predetermined level or higher. The battery case 30 is also provided with an injection port (not shown) for injecting the nonaqueous electrolyte 80. The positive electrode terminal 42 is electrically connected to the positive electrode current collector plate 42a. The negative electrode terminal 44 is electrically connected to the negative electrode current collector plate 44a. The material of the battery case 30 is, for example, a lightweight metal material with good thermal conductivity, such as aluminum. Note that FIG. 3 does not accurately represent the amount of the nonaqueous electrolyte 80.
[0063] As shown in Fig. 3 and Fig. 4, the wound electrode body 20 has a configuration in which a positive electrode sheet 50 and a negative electrode sheet 60 are overlapped with two long separator sheets 70 interposed therebetween and wound in the longitudinal direction. The positive electrode sheet 50 has a configuration in which a positive electrode active material layer 54 is formed along the longitudinal direction on one or both sides (both sides here) of a long positive electrode current collector 52. The negative electrode sheet 60 has a configuration in which a negative electrode active material layer 64 is formed along the longitudinal direction on one or both sides (both sides here) of a long negative electrode current collector 62.
[0064] The positive electrode 50 has a positive electrode active material layer non-forming portion 52a where the positive electrode active material layer 54 is not formed and the positive electrode current collector 52 is exposed. The negative electrode 60 has a negative electrode active material layer non-forming portion 62a where the negative electrode active material layer 64 is not formed and the negative electrode current collector 62 is exposed. The positive electrode active material layer non-forming portion 52a and the negative electrode active material layer non-forming portion 62a are formed so as to protrude outward from both ends in the winding axis direction (i.e., the sheet width direction perpendicular to the longitudinal direction) of the wound electrode body 20. The positive electrode active material layer non-forming portion 52a and the negative electrode active material layer non-forming portion 62a are joined to the positive electrode current collector 42a and the negative electrode current collector 44a, respectively.
[0065] The positive electrode sheet 50 is a positive electrode obtained by the manufacturing method according to the embodiment described above.
[0066] The negative electrode current collector 62 constituting the negative electrode sheet 60 may be, for example, copper foil. The negative electrode active material layer 64 includes a negative electrode active material. As the negative electrode active material, for example, a carbon material such as graphite, hard carbon, or soft carbon may be used. The negative electrode active material layer 64 may further include a binder, a thickener, or the like. As the binder, for example, styrene butadiene rubber (SBR) or the like may be used. As the thickener, for example, carboxymethyl cellulose (CMC) or the like may be used.
[0067] As the separator 70, various microporous sheets similar to those conventionally used in lithium ion secondary batteries can be used, and examples thereof include microporous resin sheets made of resins such as polyethylene (PE) and polypropylene (PP). Such microporous resin sheets may have a single layer structure or a multilayer structure of two or more layers (for example, a three-layer structure in which PP layers are laminated on both sides of a PE layer). The separator 70 may be provided with a heat-resistant layer (HRL).
[0068] The nonaqueous electrolyte 80 typically contains a nonaqueous solvent and an electrolyte salt (in other words, a supporting salt). As the nonaqueous solvent, various organic solvents such as carbonates, ethers, esters, nitriles, sulfones, and lactones that are used in electrolytes of general lithium ion secondary batteries can be used without any particular limitation. Among them, carbonates are preferable.
[0069] As the electrolyte salt, for example, lithium salts such as LiPF6, LiBF4, and lithium bis(fluorosulfonyl)imide (LiFSI) can be used, and among them, LiPF6 is preferable. The concentration of the electrolyte salt is not particularly limited, but is preferably 0.7 mol / L or more and 1.3 mol / L or less.
[0070] The nonaqueous electrolyte 80 may contain various additives other than the above-mentioned components, such as an oxalate complex, a film-forming agent such as vinylene carbonate (VC), a gas generating agent such as biphenyl (BP) or cyclohexylbenzene (CHB), a thickener, etc., as long as the effects of the present invention are not significantly impaired.
[0071] The lithium ion secondary battery 100 has excellent output characteristics. The lithium ion secondary battery 100 can be used for various applications. Suitable applications include a driving power source mounted on vehicles such as electric vehicles (BEVs), hybrid electric vehicles (HEVs), and plug-in hybrid electric vehicles (PHEVs). The lithium ion secondary battery 100 can also be used as a storage battery for small power storage devices and the like. The lithium ion secondary battery 100 can also be used in the form of a battery pack in which a plurality of lithium ion secondary batteries 100 are typically connected in series and / or in parallel.
[0072] As an example, a rectangular lithium ion secondary battery 100 including a flat wound electrode assembly 20 has been described. However, the lithium ion secondary battery disclosed herein can also be configured as a lithium ion secondary battery including a laminated electrode assembly (i.e., an electrode assembly in which multiple positive electrodes and multiple negative electrodes are alternately laminated). In addition, the nonaqueous electrolyte secondary battery disclosed herein can also be configured as a cylindrical lithium ion secondary battery, a laminated case type lithium ion secondary battery, a coin type lithium ion secondary battery, etc.
[0073] Also, a non-aqueous electrolyte secondary battery other than a lithium ion secondary battery can be constructed by using the above-mentioned positive electrode according to a known method. Furthermore, an all-solid-state secondary battery (particularly an all-solid-state lithium ion secondary battery) can be constructed by using a solid electrolyte instead of the non-aqueous electrolyte 80 according to a known method.
[0074] Examples of the present invention will be described below, but it is not intended that the present invention be limited to those shown in these examples.
[0075] [Preparation of Positive Electrode] LiNi as a positive electrode active material 1 / 3 Co 1 / 3 Mn 1 / 3O2, CNT as a conductive material, and PVdF as a binder were prepared. MWCNT with an average diameter of 13 nm were used as CNT, and average lengths of 0.1 μm, 0.3 μm, 0.5 μm, 0.7 μm, and 1.0 μm were prepared. A copolymer with a molecular weight of approximately 1.4 million was used as PVdF. MWCNT, N-methyl-2-pyrrolidone (NMP), and a pyrene ammonium derivative as a CNT dispersant were mixed by ultrasonic irradiation to prepare a CNT dispersion liquid.
[0076] LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (LNCM), CNT dispersion, and PVdF were mixed in a mass ratio of LNCM:CNT:PVdF = 98.3:1.0:0.7. An appropriate amount of NMP was added to this to obtain a positive electrode slurry. The viscosity of the positive electrode slurry was changed by changing the amount of NMP added at this time. As shown in Table 1, when CNTs with average lengths of 0.1 μm, 0.5 μm, 0.7 μm, and 1.0 μm were used, three types of positive electrode slurries with different viscosities were prepared, and when CNTs with an average length of 0.3 μm were used, four types of positive electrode slurries with different viscosities were prepared.
[0077] [Table 1]
[0078] The positive electrode slurry prepared above was applied to both sides of an aluminum foil having a thickness of 12 μm as a positive electrode current collector. At this time, a positive electrode slurry uncoated portion was provided on the aluminum foil as a lead connection portion. The amount of the positive electrode slurry applied was set so that the basis weight of the positive electrode active material layer formed was 11 mg / cm2 in total on both sides. 2 It was adjusted so that
[0079] The applied slurry was dried to form a positive electrode active material layer. The obtained sheet was pressed using a rolling roller. The rolling gap of the rolling roller was changed to adjust the porosity of the positive electrode active material layer. The obtained sheet was cut to a predetermined size to obtain a positive electrode in which a positive electrode active material layer was formed on both sides of the positive electrode current collector. In this way, several positive electrodes with different porosities of the positive electrode active material layer were produced.
[0080] [Measurement of average CNT length] The MWCNTs used were dispersed in NMP at a concentration of 0.035% by mass to prepare a measurement sample. Using this measurement sample and a flow imaging microscope "FlowCam nano" (manufactured by Yokogawa Electric Corporation), the particle size distribution was measured, and the built-in software "VisualSpreadsheet" was used to calculate the average equivalent spherical diameter (ESD) as the average length.
[0081] [Measurement of Viscosity of Positive Electrode Slurry] A cone plate was attached to a rheometer "HAAKE MARS" (manufactured by Thermo Scientific). Using this, the viscosity of the positive electrode slurry was measured at 25°C at a shear rate of 10 s -1 The measurements were performed under the following conditions.
[0082] [Measurement of Porosity of Positive Electrode Active Material Layer] Test pieces of the positive electrodes produced in each of the Examples and Comparative Examples were prepared. The porosity of the positive electrode active material layer was determined using a mercury porosimeter "Autopore V9260" (manufactured by Shimadzu Corporation).
[0083] [Preparation of evaluation battery] Graphite as a carbon-based negative electrode active material, sodium salt of carboxymethylcellulose (CMC-Na), and a dispersion of styrene butadiene rubber (SBR) were mixed in a solid mass ratio of graphite:CMC-Na:CMC=98:1:1. An appropriate amount of ion-exchanged water was further added to prepare a negative electrode slurry. The negative electrode slurry was applied to both sides of a copper foil with a thickness of 8 μm as a negative electrode current collector. At this time, a negative electrode slurry uncoated portion was provided on the copper foil as a lead connection portion.
[0084] The applied paste was dried to form a negative electrode active material layer. The obtained sheet was pressed with a roller and then cut to a predetermined size to obtain a negative electrode in which a negative electrode active material layer was formed on both sides of the negative electrode current collector. The packing density of the negative electrode active material layer was 1.20 g / cm. 3 It was.
[0085] A lead was attached to each of the positive and negative electrodes prepared above. A single-layer polypropylene separator was prepared. The positive and negative electrodes were alternately stacked one by one with the separators interposed therebetween to prepare a laminated electrode body.
[0086] A mixed solvent containing ethylene carbonate (EC), dimethyl carbonate (DMC), and ethyl methyl carbonate (EMC) in a volume ratio of 25:35:40 was prepared. Vinylene carbonate was dissolved in this mixed solvent at a concentration of 1 mass%, lithium bis(oxalate)borate was dissolved in a concentration of 0.8 mass%, and LiPF6 as a supporting salt was dissolved in a concentration of 1.15 mol / L. This resulted in a nonaqueous electrolyte.
[0087] The laminated electrode body and the non-aqueous electrolyte solution thus prepared were placed in a square battery case and sealed to obtain a square lithium ion secondary battery for evaluation. The amount of the non-aqueous electrolyte solution injected was 9.0 g / Ah.
[0088] <Output resistance measurement> Each evaluation lithium-ion secondary battery was adjusted to a SOC (State of charge) of 50% by constant current constant voltage (CC-CV) charging, and then placed in an environment of 25°C. Discharging was performed for 10 seconds at a current value of 50C, and the voltage drop amount ΔV at this time was obtained. Using this voltage drop amount ΔV and the current value, the initial output resistance value of each evaluation secondary battery was calculated. The results are shown in Figures 5 to 9. Note that the smaller the initial output resistance value, the higher the output of the secondary battery, and therefore the more excellent the output characteristics.
[0089] 5 to 9 are graphs plotting the initial output resistance (μΩ) versus the porosity (%) of the positive electrode active material layer when the average CNT lengths are 0.1 μm, 0.3 μm, 0.5 μm, 0.7 μm, and 1.0 μm, respectively.
[0090] As shown in the graphs of Figures 5 and 9, when the average length of the CNTs was 0.1 μm and 1.0 μm, the initial output resistance tended to increase as the porosity increased, regardless of the viscosity of the positive electrode slurry. On the other hand, in the graph of Figure 6, where the average length of the CNTs was 0.3 μm, when the viscosity of the positive electrode slurry was 0.7 Pa·s and 5.7 Pa·s, the initial output resistance also tended to increase as the porosity increased. However, when the viscosity of the positive electrode slurry was 2.1 Pa·s and 4.2 Pa·s, a different trend was observed, and a decrease in the initial output resistance was observed in the range of porosity of 42.5% to 54.5%, as shown in the elliptical dashed frame. In the graph of Figure 7, where the average length of the CNTs was 0.5 μm, when the viscosity of the positive electrode slurry was 3.2 Pa·s, a decrease in the initial output resistance was observed in the range of porosity of 42.5% to 54.5%, as shown in the elliptical dashed frame, as in Figure 6. In the graph of Figure 8, where the average length of the CNTs is 0.7 μm, similarly to Figure 6, when the viscosity of the positive electrode slurry was 4.2 Pa s, a decrease in the initial output resistance was observed in the porosity range of 42.5% to 54.5%, as shown in the elliptical dashed frame.
[0091] The above results show that the output resistance is specifically reduced when CNTs with an average length of 0.3 μm to 0.7 μm are used, a positive electrode slurry with a viscosity of 2.1 Pa·s to 4.2 Pa·s at 25°C is used, and the positive electrode active material layer is pressed so that the porosity is 42.5% to 54.5%.
[0092] Considering these results, the reason why the output resistance is large when the CNT length is 0.1 μm is because the CNTs are too short and the conductive path between the positive electrode active material is insufficient. The reason why the initial output resistance increases as the porosity increases is thought to be because the positive electrode active material particles become sparser with increasing porosity, reducing the conductive path.
[0093] The reason why the output resistance is large when the CNT length is 1.0 μm is because the CNTs are not sufficiently dispersed in the positive electrode active material layer. In particular, when the CNT length is large, the dispersibility decreases, and further decrease in dispersibility due to re-aggregation is added. The reason why the initial output resistance increases as the porosity increases is thought to be because the positive electrode active material particles become sparser with increasing porosity, reducing the conductive path.
[0094] When the CNT length is 0.3μm~0.7μm and the viscosity is less than 2.1Pa·s, the output resistance is high, presumably because CNT migration occurs during slurry application, causing the CNTs to be unevenly dispersed.When the CNT length is 0.3μm~0.7μm and the viscosity is more than 4.2Pa·s, the output resistance is high, presumably because the viscosity of the slurry is too high, causing the CNTs to be unevenly dispersed in the positive electrode active material layer.
[0095] When the CNT length is 0.3 μm to 0.7 μm, the viscosity is 2.1 Pa·s to 4.2 Pa·s, and the porosity is 42.5% to 54.5%, the output resistance is small. This is thought to be because, even when the porosity is relatively high, the CNT length is appropriate, so that a good conductive path is formed in the positive electrode active material layer, and because there are appropriate voids in the positive electrode active material layer, it becomes easier for Li ions in the electrolyte to move when the lithium-ion secondary battery is discharged.
[0096] From the above, it can be seen that the method for producing a positive electrode disclosed herein makes it possible to produce a positive electrode that can impart excellent output characteristics to a lithium ion secondary battery.
[0097] Although the specific examples of the present invention have been described in detail above, these are merely examples and do not limit the scope of the claims. The technology described in the claims includes various modifications and alterations of the specific examples exemplified above.
[0098] That is, the method for producing a positive electrode and the positive electrode disclosed herein include the following items [1] to [5]. [1] A step of applying a positive electrode slurry containing a positive electrode active material, carbon nanotubes, and a dispersion medium to a positive electrode current collector; drying the applied positive electrode slurry to form a positive electrode active material layer; and pressing the positive electrode active material layer so that the positive electrode active material layer has a porosity of 42.5% to 54.5%, The carbon nanotubes have an average length of 0.3 μm to 0.7 μm; The positive electrode slurry has a viscosity of 2.1 Pa s to 4.2 Pa s at 25°C. Manufacturing method. [2] The method according to item [1], wherein the positive electrode active material layer is pressed so that the positive electrode active material layer has a porosity of 46% to 53%. [3] The method according to item [1] or [2], wherein the dispersion medium is N-methyl-2-pyrrolidone. [4] The method according to any one of items [1] to [3], wherein the positive electrode is a positive electrode of a lithium ion secondary battery. [5] A positive electrode comprising a positive electrode current collector and a positive electrode active material layer supported on the positive electrode current collector, The positive electrode active material layer contains a positive electrode active material and carbon nanotubes, The positive electrode active material layer has a porosity of 42.5% to 54.5%, The carbon nanotubes have an average length of 0.3 μm to 0.7 μm; The positive electrode is formed using a positive electrode slurry having a viscosity at 25°C of 2.1 Pa·s to 4.2 Pa·s. [Explanation of symbols]
[0099] 20 Wound electrode body 30 Battery case 36 Safety valve 42 Positive terminal 42a Positive current collector 44 Negative terminal 44a Negative current collector plate 50 Positive electrode sheet (positive electrode) 52 Positive electrode current collector 52a Portion where positive electrode active material layer is not formed 54 Cathode active material layer 60 Negative electrode sheet (negative electrode) 62 Negative electrode current collector 62a Part where negative electrode active material layer is not formed 64 Negative electrode active material layer 70 Separator sheet (separator) 80 Non-aqueous electrolytes 100 Lithium-ion secondary battery
Claims
1. A step of applying a positive electrode slurry containing a positive electrode active material, carbon nanotubes, and a dispersion medium to a positive electrode current collector; drying the applied positive electrode slurry to form a positive electrode active material layer; and pressing the positive electrode active material layer so that the positive electrode active material layer has a porosity of 42.5% to 54.5%, The carbon nanotubes have an average length of 0.3 μm to 0.7 μm; The viscosity of the positive electrode slurry at 25°C is 2.1 Pa s to 4.2 Pa s; Manufacturing method.
2. The method according to claim 1, wherein the positive electrode active material layer is pressed so that the positive electrode active material layer has a porosity of 46% to 53%.
3. The method according to claim 1, wherein the dispersion medium is N-methyl-2-pyrrolidone.
4. The method according to claim 1 , wherein the positive electrode is a positive electrode of a lithium ion secondary battery.
5. A positive electrode comprising a positive electrode current collector and a positive electrode active material layer supported on the positive electrode current collector, The positive electrode active material layer contains a positive electrode active material and carbon nanotubes, The positive electrode active material layer has a porosity of 42.5% to 54.5%; The carbon nanotubes have an average length of 0.3 μm to 0.7 μm; The positive electrode is formed using a positive electrode slurry having a viscosity of 2.1 Pa·s to 4.2 Pa·s at 25° C.
Citation Information
Patent Citations
Lithium secondary battery, power storage device including lithium secondary battery, and method for manufacturing lithium secondary battery
JP2016131123A
Positive electrode for nonaqueous electrolyte secondary battery
JP2018055836A
Positive electrode for lithium-ion secondary battery, lithium-ion secondary battery, and manufacturing method of positive electrode for lithium-ion secondary battery
JP2022055888A
Positive electrode for lithium ion secondary battery, lithium ion secondary battery, and manufacturing method of positive electrode for lithium ion secondary battery
JP2022055890A
Electrode for lithium ion secondary cell, method for preparing paste for said electrode and method for manufacturing said electrode
WO2013179909A1
